Relationship between Pain and Serum Ferritin Levels in Adult Transfusion-Dependent Thalassemia - Shenny Dianathasari Santoso; Uni Gamayani; Asep Nugraha Hermawan; Pandji Irani Fianza; Aih Cahyani; Lisda Amalia; Yusuf Wibisono; Ramdan Panigoro (Global Medical & Health Communication (GMHC), 2021)
Patients with transfusion-dependent thalassemia (TDT) may experience an increase in ferritin due to shorter erythrocyte lifespan and lysis, as well as side effects of transfusion. Increasing ferritin can cause various complications, including pain, which can develop into chronic pain and interfere with life quality. This study aims to determine the relationship between pain and serum ferritin levels in adults with TDT. This study was an analytical observational study using a cross-sectional design on adult TDT patients with pain who came to the Hemato-Oncology Clinic of Dr. Hasan Sadikin General Hospital Bandung. This research was conducted from March to June 2021. All subjects were assisted to fill out the Indonesian version of the Brief Pain Inventory Short Form (BPI-SF) questionnaire before transfusion. Ferritin levels in the last three months were obtained from medical records. If more than three months, serum ferritin levels were examined. Ferritin levels and BPI-SF scores were then correlated using the Pearson test. The study was conducted on 51 adult TDT patients with pain, and the average value of ferritin levels in research subjects is 5081±2929 g/L. There was a relationship between pain (the dimensions of pain interfere with life on the BPI-SF score) and an increase in ferritin levels (p=0.042, r=0.29). The results showed there is a relationship between pain and serum ferritin levels. Regular consumption of iron chelation tablets can reduce ferritin levels and improve the quality of life for adults with TDT. HUBUNGAN NYERI DENGAN KADAR FERITIN SERUM PADA PENYANDANG TRANSFUSION-DEPENDENT THALASSEMIA DEWASAPenyandang transfusion-dependent thalassemia (TDT) dapat mengalami peningkatan feritin akibat umur eritrosit yang lebih pendek dan mudah lisis, serta efek samping terhadap pemberian transfusi. Peningkatan feritin tersebut dapat menyebabkan berbagai komplikasi di antaranya nyeri yang dapat berkembang menjadi nyeri kronik dan mengganggu kualitas hidup. Penelitian ini bertujuan mengetahui hubungan nyeri dengan kadar feritin serum pada penyandang TDT dewasa. Penelitian dengan observasional analitik menggunakan rancangan potong lintang pada penyandang TDT dewasa dengan nyeri yang datang ke Klinik Hemato-Onkologi RSUP Dr. Hasan Sadikin Bandung. Penelitian dilakukan dari Maret hingga Juni 2021. Seluruh subjek dilakukan pendampingan untuk mengisi kuesioner Brief Pain Inventory Short Form (BPI-SF) versi Indonesia sebelum transfusi. Kadar feritin dalam tiga bulan terakhir didapatkan dari rekam medis dan bila lebih dari tiga bulan dilakukan pemeriksaan kadar feritin serum. Kadar feritin dan skor BPI-SF kemudian dikorelasikan menggunakan Uji Pearson. Penelitian dilakukan kepada 51 penyandang TDT dewasa dengan gejala nyeri dan didapatkan nilai rerata kadar feritin pada subjek penelitian adalah 5081±2929 μg/L. Hasil penelitian memperlihatkan terdapat hubungan antara nyeri (dimensi efek nyeri terhadap kehidupan) dan peningkatan kadar feritin (p=0,042; r=0,29). Hasil penelitian menunjukkan terdapat hubungan antara nyeri dan kadar feritin serum. Konsumsi tablet kelasi besi secara rutin dapat menurunkan kadar feritin dan memperbaiki kualitas hidup penyandang TDT dewasa.